Proxy Framework for Database Extension: Database-Independent Function Extension - Phoonsarakun, Pinaet; Adam, Alexander; Khaesawad, Attaporn; Chinodom, Seree (Transactions on Engineering and Computing Sciences, 2014)
This paper presents a proxy framework, which allows introducing various functionalities in an existing database system and application environment. By using a proxy not interfering with the application and with the database are necessary. An abstraction layer is introduced to make functional modules, database independent, and illustrates its use in two examples – index integration and a result cache. Finally, an overview of the results that have been achieved is given.